PEWARNAAN TITIK PADA GRAF UNTUK PENYUSUNAN MENU MAKANAN - Siti Amiroch; Evi Eka Andini (Unisda Journal of Mathematics and Computer Science (UJMC), 2016)
A balanced diet encourage the creation of eating behavior that optimizes the intake and absorption of nutrients by consuming healthy foods corresponding proportion in each serving. To realize the diet required a proper diet plan and balanced with a method of food combining. By applying the coloring point on the graph using the Welch-Powell algorithm and the combination of mathematics imposed on the menu sequence can provide a solution to preparing the menu that varies with the amount of calories that is appropriate and balanced according to the rules low calorie diet. The results obtained from the third combination meal menu is 108 varied menu of breakfast, lunch menu variations 162, and 16 variations of the dinner menu. With respect to the number of calories for all three, each taken ve menus to be combined in a week. Obtained result V1, V5, V8, V9 with the color red dot on consumption on Monday, Tuesday, and Wednesday. V2, V3 and V7 with the color green dot inconsumption on Thursday and Friday, and V4, V6 and V10 which has a yellow color in consumption on Saturday and Sunday.